2013
DOI: 10.1016/j.jacc.2013.02.089
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Left Atrial Appendage Closure With the AMPLATZER Cardiac Plug Device in Patients With Nonvalvular Atrial Fibrillation and Contraindications to Anticoagulation Therapy

Abstract: In patients with nonvalvular atrial fibrillation at high risk of cardioembolic events and absolute contraindications to anticoagulation, LAAC using the ACP device followed by dual-/single-antiplatelet therapy was associated with a low rate of embolic and bleeding events after a mean follow-up of 20 months. No cases of severe residual leak or device thrombosis were observed at the 6-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
141
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(163 citation statements)
references
References 23 publications
15
141
4
3
Order By: Relevance
“…34 The device was successfully implanted in 51 of 52 patients (98%). Device embolization was observed in 1 patient (1.9%).…”
Section: Results Of Clinical Trials the Protect-af (Watchman Left Atrmentioning
confidence: 99%
“…34 The device was successfully implanted in 51 of 52 patients (98%). Device embolization was observed in 1 patient (1.9%).…”
Section: Results Of Clinical Trials the Protect-af (Watchman Left Atrmentioning
confidence: 99%
“…Nowadays, oral anticoagulation still remains the state-of-the-art therapy for patients with AF. Since the first percutaneous LAA occlusion (LAAO) in 2002 [1] many studies have shown the safety and efficacy of this therapy using different closure devices [2][3][4][5][6][7][8][9]. Percutaneous LAAO is a valuable therapeutic option for selected high-risk patients with AF and contraindications for oral anticoagulation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the double disc structure of the ACP, which contributes to better sealing. 12 Significant leakage (≥5 mm), however, was not detected and the incidence of clinical events was similar for both devices. Interestingly, all major leakages (3-5 mm) developed in patients in whom no peridevice leakage was detected immediately after the procedure.…”
Section: Peridevice Leakagementioning
confidence: 87%
“…Several possible explanations include incomplete device endothelialization, anatomical remodeling of LAA ostium over time, use of an undersized device without periprocedural residual leak due to LAA contraction immediately after implantation, and low left ventricular ejection fraction, which might increase the LA dimensions. 12 In general, the presence of peridevice leakage (<5 mm) was not clinically relevant, indicating that anticoagulation can be discontinued at the discretion of physicians. Significant leakage (≥5 mm) and the progressive increase of ble procedure as an alternative to anticoagulation in patients at high risk for bleeding or contraindication to anticoagulation, or in whom anticoagulation failed to prevent stroke.…”
Section: Peridevice Leakagementioning
confidence: 97%